(untitled) (Fiep Bulletin - online, 2011)
Summary: This is a literature review in order to describe about the stress and the benefits of physical activity as a strategy for preventing and dealing with this problem. Stress is now considered a disease that affects many people regardless of their life cycle, particularly in adulthood, usually on the basis of the wide family and work pressures and other aggravating today. The study is descriptive, bibliographical, seeking articles on thematic databases, online journals and other related sites, using the terms physical activity, exercise and stress. It follows that to prevent and cope with stress, physical activity confers undeniable benefits in physical, mental and emotional development of regular practitioners, minimizing health risks, increasing the body’s functions and, ultimately, maximizing quality of life.